Caspase-1 cleaves PPARγ for potentiating the pro-tumor action of TAMs - Zhiyuan Niu (Nature Portfolio, 2017)
Tumor associated macrophages (TAMs) promote cancer progression. Here, the author show that caspase-1 promotes TAMs differentiation by attenuating medium-chain acyl-CoA dehydrogenase activity and that inhibition of this axis results in suppression of tumour growth in a transgenic mouse model of breast cancer.